1989
DOI: 10.1029/jb094ib05p05908
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic centers of southwestern Nevada: Evolution of understanding, 1960–1988

Abstract: Since about 1960, geologists of the U.S. Geological Survey and, more recently, those of Los Alamos and Lawrence Livermore national laboratories, supported largely by the U.S. Department of Energy (DOE) and its predecessors, have been unraveling a complex series of ash flow sheets, lavas, and related calderas in the southwestern Nevada volcanic field in and near the Nevada Test Site (NTS). Extensive detailed geologic mapping aided in delineation of four major calderas: Silent Canyon (∼14 Ma), Timber Mountain‐Oa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 72 publications
1
37
0
Order By: Relevance
“…The entire stratigraphic and lithologic package is offset by younger high-angle normal faults. Recent summaries of the geology and hydrogeology of this volcanic field are contained in Laczniak et al (1996);Sawyer et al (1994);Ferguson et al (1994); Noble et al (1991); Byers et al (1989);and Sawyer and Sargent (1989). Two major buried caIderas of the southwestern Nevada volcanic field, which together form the Silent Canyon caldera complex, are located in the subsurface of the Pahute Mesa underground test area (Figure 3).…”
Section: Regwnal Geologic Settingmentioning
confidence: 99%
“…The entire stratigraphic and lithologic package is offset by younger high-angle normal faults. Recent summaries of the geology and hydrogeology of this volcanic field are contained in Laczniak et al (1996);Sawyer et al (1994);Ferguson et al (1994); Noble et al (1991); Byers et al (1989);and Sawyer and Sargent (1989). Two major buried caIderas of the southwestern Nevada volcanic field, which together form the Silent Canyon caldera complex, are located in the subsurface of the Pahute Mesa underground test area (Figure 3).…”
Section: Regwnal Geologic Settingmentioning
confidence: 99%
“…Refinement of the stratigraphy of the area was a continuous process during the decades in which geoscientists associated with the Weapons Testing Program worked to understand the complex volcanic setting (documented by Byers et al, 1989). The need to develop detailed geologic models in support of the Underground Test Area (UGTA) Sub-Project (see Chapter 12 of the main body of this document) intensified this process, and the recognition of smaller and smaller distinct volcanic units permitted a greater understanding of the three-dimensional configuration of the various types of rocks, which has been incorporated into the geologic framework.…”
Section: A12 Stratigraphymentioning
confidence: 99%
“…Refinement of the stratigraphy of the area was a continuous process during the decades in which geoscientists associated with the Weapons Testing Program (WTP) worked to understand the complex volcanic setting (documented by Byers et al, 1989). The need to develop detailed geologic models in support of the Underground Test Area (UGTA) Project (see Section 13) intensified this process, and the recognition of smaller and smaller distinct volcanic units permitted a greater understanding of the three-dimensional configuration of the various types of rocks, which has been incorporated into the geologic framework.…”
Section: A42 Stratigraphymentioning
confidence: 99%
“…This summary was compiled from various sources, including BN (2001a), Gonzales and Drellack (1999), Winograd and Thordarson (1975), Laczniak et al, (1996), Byers et al, (1989), andCole (1997) where additional information can be found.…”
Section: A552 Yucca Flat/climax Mine Underground Test Areamentioning
confidence: 99%